2011
DOI: 10.1097/acm.0b013e318212c2c9
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Transition: The Experience and Impact of Frequent Changes in the Inpatient Learning Environment

Abstract: These findings challenge the value of the traditional "rotating" model in residency. As residents adapt to frequent transitioning, they implicitly learn to value flexibility and efficiency over relationship building and deep system knowledge. These findings raise significant implications for professional development and patient care and highlight an important element of the hidden curriculum embedded within the current training model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 22 publications
5
128
0
1
Order By: Relevance
“…The workplace structure and pace can further impede performance assessment. 3,4 Entrustable professional activities (EPAs) are a strategy to operationalize competencies and milestones in the workplace and focus supervisors and learners on key activities to be assessed. 5,6 Graduate medical educators have started to implement EPAs as a framework for assessment across specialties.…”
Section: Introductionmentioning
confidence: 99%
“…The workplace structure and pace can further impede performance assessment. 3,4 Entrustable professional activities (EPAs) are a strategy to operationalize competencies and milestones in the workplace and focus supervisors and learners on key activities to be assessed. 5,6 Graduate medical educators have started to implement EPAs as a framework for assessment across specialties.…”
Section: Introductionmentioning
confidence: 99%
“…Kennedy et al [24] identified that faculty grant residents independence based on the resident's knowledge and skill as well as their insight into limitations. Clearly, long rotations are often required to build sufficient relationships to determine a trainee's strengths and limitations [5]; brief and fragmented facultyÀresident contact is often not an ideal way to draw valid, reliable conclusions [22]; however, such close contact between a single resident and faculty can be limited, making a simulated entrustable professional activity valuable in determining a resident's abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the entire team turns over every 2 to 4 weeks, and continuity is disrupted daily, detracting from residents' ability to relate to patients. 19 With the adoption of the Accreditation Council for Graduate Medical Education (ACGME) duty hour restrictions, handoffs have increased, 20 and patients are often confused about who their physicians are and who is ''in charge.'' 21,22 While reduced hours certainly have positive consequences, residents have fewer opportunities to connect meaningfully with patients and witness the longitudinal course of illnesses.…”
Section: The Current Reality: Discontinuities Of Carementioning
confidence: 99%